Road Infrastructure and Tourism in Nigeria: Evidence from Ikogosi Warm Spring, Ekiti State - Olabosinde, Samuel Taiwo (Eco-Tourism and Sustainable Development, 2025)
This study explores the influence of road transport infrastructure quality on tourism patronage at Ikogosi Warm Spring, a notable eco-tourism destination in Ekiti State, Nigeria. The importance of accessible and reliable road infrastructure in stimulating tourism growth, particularly in rural settings, cannot be overemphasized. Data were collected from 150 tourists through structured questionnaires and analyzed using multiple regression techniques. The analysis focused on five key dimensions of road infrastructure: road surface condition, signage and lighting, connectivity and accessibility, safety and security, and government investment in maintenance. Findings revealed that poor road surface conditions and negatively perceived government road maintenance significantly deterred tourist visits. In contrast, signage and lighting, connectivity, and safety showed limited statistical influence on patronage levels. These outcomes suggest that tourists are particularly responsive to the physical condition of access roads and disruptions caused by poorly executed or untimely government interventions. Based on these insights, the study recommends that tourism-related government agencies prioritize timely road surface improvements and adopt more transparent, visitor-sensitive approaches to road works. Attention should also be given to functional signage, safe access routes, and consistent road maintenance policies. This study contributes to the discourse on transport-tourism linkages by highlighting the complex interplay between infrastructure quality and visitor behavior, offering policy-relevant insights for enhancing sustainable tourism development in Nigeria’s interior destinations.